A quality model for component-based software - Ali, Mohamed Abdullahi (2019)
In Component Based Software Development (CBSD), applications are built from existing components by assembling and replacing interoperable parts. Now day’s component based software engineering considers one of the growing approaches for software development, its Reusable components that minimize implementation time, cost. To evaluate design quality of the component is important because it has main impact to the final implementation therefore, the existing component quality models all of them are based on generic attributes of the component so that none of them were discussed attributes that specific at design level for the component that has the main influence to the final product hence designing high quality component needs to get component quality model that specific in design level that based on design attributes for component. This thesis proposed Quality Model for Component-based Software at design level. To evaluate this quality model, it implemented a prototype metrics tool. Finally, this prototype metrics tool will help the developers to detect the design problems and indication the goodness of design early, hence good design leads to ease for maintenance and improve the quality of the final product.